The Model of Inpatient Unit Service Quality at the Indonesian Christian University General Hospital Based on Malcolm Balridge Criteria - Fransisca Fransisca; Rokiah Kusumapradja; Endang Ruswanti (Jurnal sosial dan sains, 2023)
Background: In 2022, there was a decrease in the satisfaction rate and BOR in the UKI General Hospital inpatient unit. Improvements in the quality of health are needed. The Malcolm Balridge criteria is the method of measuring the quality of health services from the United States. The malcolm balridge criteria has a dynamic framework and provide as an independent and comprehensive assessment. Purpose: Seven criteria are leadership, strategic planning, patient focus, measurement, analysis and knowledge management, workforce focus, work operation focus and organizational performance results. The researcher measured the quality assessment at the UKI General Hospital inpatient unit based on Malcolm Balridge’s Criteria. Method: This research was conducted on 70 respondents in the inpatient unit, using a qualitative approach with univariate analysis and scoring based on Malcolm Balridge’s Criteria. Results: The score was 276.5 out of 1000 points. It is an early result position, the poor quality. There are gaps in the approach and implementation stages as well as the deployment in several categories. Criteria that are below the average value are workforce focus and organizational performance results. Conclusion: The purpose was to provide an overview of the model development for the quality health services in the UKI General Hospital inpatient unit based on Malcolm Balridg’s criteria.